2014
DOI: 10.1007/s12185-014-1614-y
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Prolonged thrombocytopenia after living donor liver transplantation is a strong prognostic predictor irrespective of splenectomy: the significance of ADAMTS13 and graft function

Abstract: production due to hepatocyte dysfunction, irrespective of splenectomy." Errors have subsequently been identified in the original publication, and the following corrections should be noted: 1. The revised Figs. 1 and 5 and Tables 1, 2, 3 and 4 were replaced with this erratum. 2. References [18] and [27] should be replaced as below. 18. Takei Y, Marzi I, Gao WS, Gores GJ, Lemasters JJ, Thurman RG. Leukocyte adhesion and cell death following orthotopic liver transplantation in the rat. Transplantation. 1991;51(5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Marubashi et al [31] found that seven patients who underwent simultaneous splenectomy showed a remarkable increase in their platelet counts after LDLT on POD14, with the peak in the platelet count seen at POD28. We encountered several LDLT patients who had suffered from prolonged thrombocytopenia even after splenectomy [27]. Our study also showed that the platelet counts after splenectomy in operations other than LDLT significantly increased on POD7 and peaked on POD14.…”
Section: Splenectomy and Thrombocytopeniasupporting
confidence: 59%
See 4 more Smart Citations
“…Marubashi et al [31] found that seven patients who underwent simultaneous splenectomy showed a remarkable increase in their platelet counts after LDLT on POD14, with the peak in the platelet count seen at POD28. We encountered several LDLT patients who had suffered from prolonged thrombocytopenia even after splenectomy [27]. Our study also showed that the platelet counts after splenectomy in operations other than LDLT significantly increased on POD7 and peaked on POD14.…”
Section: Splenectomy and Thrombocytopeniasupporting
confidence: 59%
“…Although the patients in our study gradually recovered from early thrombocytopenia after LDLT within 14 days, there were several patients who showed a delayed recovery of their platelet count, exhibiting prolonged thrombocytopenia [27]. Adult LDLT patients were divided into 2 groups based on their platelet counts (100 × 10 3 / μL) on POD14: high-and low-platelet (HP and LP, respectively) groups.…”
Section: Thrombocytopenia and Patient Outcomesmentioning
confidence: 93%
See 3 more Smart Citations